2006
DOI: 10.4049/jimmunol.176.1.256
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Cytokine p43 Induces IL-12 Production in Macrophages via NF-κB Activation, Leading to Enhanced IFN-γ Production in CD4+ T Cells

Abstract: Recently, we determined that p43, an auxiliary factor of mammalian multiaminoacyl-tRNA synthetases, is secreted, and functions as a novel pleiotropic cytokine. In this study, we have attempted to characterize the effects of p43 on the generation of IL-12 in mouse macrophages. p43 was determined to induce significant IL-12 production from mouse macrophages in a dose-dependent manner. The stimulatory effect of p43 on the activation of IL-12p40 promoter was mapped to a region harboring an NF-κB binding site. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 43 publications
(34 reference statements)
3
36
0
Order By: Relevance
“…We have previously demonstrated that AIMP1 induced IL-12 production in mouse macrophages via the activation of NF-B (20). Consistent with these results, AIMP1 significantly increased the binding of the NF-B transcription factor to the B site in DCs, as measured by an electrophoretic mobility assay (data not shown).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We have previously demonstrated that AIMP1 induced IL-12 production in mouse macrophages via the activation of NF-B (20). Consistent with these results, AIMP1 significantly increased the binding of the NF-B transcription factor to the B site in DCs, as measured by an electrophoretic mobility assay (data not shown).…”
Section: Discussionsupporting
confidence: 76%
“…Previously we found that AIMP1 stimulated macrophages to secrete IL-12, and that AIMP1-activated macrophages induced the IFN-␥ production from keyhole limpet hemocyanin (KLH)-primed Th cells (20). It is not clear at present whether AIMP1 is involved in the maturation and activation of DCs, which lead to regulate T cell responses.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 96%
“…The in vivo administration of AIMP1 induced CD69 expression on splenic B cells, indicating that AIMP1 is a critical B cell activator. We previously reported that AIMP1 activates macrophages and DCs (12,13). Because stimulated macrophages and DCs are known to express BAFF and APRIL (18), the in vivo data might be, at least in part, mediated by these cells.…”
Section: Discussionmentioning
confidence: 99%
“…AIMP1 is also secreted and has been shown to have various activities, including effects on wound healing (10) and glucagon-like functions that control blood glucose levels (11). Furthermore, we demonstrated that AIMP1 functions as a proinflammatory cytokine that induces macrophage activation, DC maturation, and IL-12 production, indicating that AIMP1 is a novel immune modulator (12,13). However, it is unclear whether AIMP1 affects other APCs, such as B cells.…”
mentioning
confidence: 86%
“…AIMP1 stimulates monocytes/macrophages via activation of p38 MAPK, ERK, and NFjB, inducing secretion of proinflammatory cytokines such as tumor necrosis factor-a (TNFa), interleukin-8 (IL-8), and macrophage chemotactic protein-1 (24,29,30). AIMP1 also induces maturation of DCs and enhances production of IL-6 and IL-12 which are critical cytokines for the suppression of cancer prevalence (31). With this immune stimulatory activity, systemic infusion of AIMP1 into nude mice harboring human cancer cell line suppressed tumor growth through activation of immune system (32).…”
Section: Structure and Regulatory Functions Of Aimp1mentioning
confidence: 99%